Oncoplastic and Reconstructive Surgery for Breast Cancer The Institut Curie Experience - Fitoussi, A.; Berry, MG.; Couturaud, B.; Salmon, R. J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
'Oncoplastic and Reconstructive Surgery for Breast Cancer describes the reconstructive techniques that have been refined over the past decade by surgeons in a very high volume unit. It provides clear descriptions of all the available techniques. With proven experience in the procedures described and detailed scientific evaluation, it furthermore provides evidence-based literature reviews. The book starts with the relevant anatomical background and passes through all the major oncoplastic and reconstructive procedures available to the breast cancer patient. It includes management of breast and nipple-areolar complex reconstruction in addition to symmetrising surgery and the new technique of fat transfer. It also covers all multidisciplinary aspects and genetics thus giving an up-to-date status report.
Anatomical Review -- Standard Breast Conserving Surgery -- Oncoplastic Breast Surgery -- Breast Reconstruction: Immediate and Delayed -- Particular Cases -- Aesthetic Sequelae of Breast-Conserving Therapy (ASBCT) -- Second-Stage Surgery -- Lipomodelage and Breast Surgery -- Prophylactic Surgery -- Multidisciplinarity -- Prophylactic Mastectomy and BRCA1 or BRCA2 Gene Mutations.
Keywords: Medicine; Gynecology; Surgery; Plastic surgery; Surgical oncology; Medicine & Public Health; Plastic Surgery; Surgery; Surgical Oncology; Gynecology; Electronic books